Pengaruh Penerbitan Obligasi Syariah (Sukuk) terhadap Reaksi Pasar Modal Indonesia Tahun 2009-2013 - Savitri, Enni (Jurnal Aplikasi Manajemen, 2015)
The aim of this study was to determine the effect of the nominal value and ratings ofIslamic bonds or sukuk on the stock reaction (cumulative abnormal return). This study wasconducted to investigate empirically the effect of the issuance of Islamic bonds (sukuk) to thecapital market reaction is carried out research on the companies that issue Islamic bondsand listed on the Indonesia Stock Exchange (BEI), there are 28 samples are used as aresearch sample. Data collection techniques in this research using secondary data, and thedata used in this research is financial statements, a list of daily stock price, the value of theissuance of Islamic bonds, Islamic bonds issuance and rating. The results showed that thevariable nominal value of Islamic bonds and the ratings did not have a significant influenceon stock reaction. This is proved by the effect of the issuance of Islamic bonds to the reactionof the capital markets which amounted to 1.2%, while 98.8% are influenced by other factorsnot measured in the study.